Competence and public service orientation as determinants of leg-islative performance: a study of members of the Kerinci regency regional house of representatives - Novandri Panca Putra; Suhelmi Helia (JPGI (Jurnal Penelitian Guru Indonesia), 2026)
Legislator performance is a critical determinant of the effectiveness of regional development oversight, yet it remains underexplored empirically at the regency-level legislature. This study examines the effect of competence and public service orientation on legislator performance among members of the Kerinci Regency Regional House of Representatives (DPRD), both partially and simultaneously. A quantitative associative approach was employed with a population of 30 DPRD members selected through total sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that competence has a positive and significant effect on legislator performance (t = 3.122; sig = 0.004), as does public service orientation (t = 9.649; sig = 0.000). Simultaneously, both variables significantly affect performance (F = 49.613; sig = 0.000), contributing 78.6%. These findings confirm the need to strengthen legislators’ technical capacity and public-interest orientation simultaneously to optimize legislative oversight at the regional level.